Perancangan dan Pembuatan Sistem Informasi KLPCM di Rumah Sakit Citra Husada Jember - Mohammad Maulana Rifki Fadilah; Muhammad Yunus; Mudafiq Riyan Pratama; Demiawan Rachmatta Putro Mudiono (Indonesian Journal Publisher, 2025)
Incomplete filling of medical records (KLPCM) is an indicator of the quality of nursing care. Citra Husada Hospital experienced an 83.5% medical record incompleteness rate in the fourth trimester of 2022, with the highest form of incompleteness occurring in the pre-surgical assessment at 59.68%. Furthermore, the KLPCM review process still relies on Excel, which presents several drawbacks, such as non-specific columns, a lack of user-friendliness, and the need for high precision due to small input fields. As a result, the KLPCM review process is time-consuming and prone to input errors. Based on these issues, a KLPCM information system is needed at Citra Husada Hospital in Jember. The system development method used is the Prototype method, with data collection techniques including interviews, observation, and documentation. The system is web-based, developed using the PHP programming language with the Laravel framework and a MySQL database. The system's features include user management, doctor management, form and form content management, patient management, KLPCM medical record analysis, reports, and incompleteness notifications. The system testing results, conducted using black box testing, showed that all functionalities work properly.